Improved thermal isolation of silicon suspended platforms for an all-silicon thermoelectric microgenerator based on large scale integration of Si nanowires as thermoelectric material. (November 2015) - Fonseca, L; Donmez, I; Salleras, M; Calaza, C; Gadea, G; Santos, J D; Morata, A; Tarancon, A
Abstract: Special suspended micro-platforms have been designed as a part of silicon compatible planar thermoelectric microgenerators. Bottom-up grown silicon nanowires are going to bridge in the future such platforms to the surrounding silicon bulk rim. They will act as thermoelectric material thus configuring an all-silicon thermoelectric device. In the new platform design other additional bridging elements (usually auxiliary support silicon beams) are substituted by low conductance thin film dielectric membranes in order to maximize the temperature difference developed between both areas. These membranes follow a sieve-like design that allows fabricating them with a short additional wet anisotropic etch step.